A NARRATIVE LITERATURE REVIEW OF CONTEMPORARY HISTORIC-EPISTEMOLOGICAL STUDIES ON ALGEBRA: SOME IMPLICATIONS FOR MATHEMATICS EDUCATION - López Acosta, Luis Alberto (Universidad de Costa Rica, 2024)
Various approaches to teaching and learning of Algebra within Mathematics Education come from classical studies in the History of Mathematics. Consequently, in this second discipline, a narrative literature review of contemporary sources, between 2000 and 2018, in prominent data bases and journals was carried out to identify new elements that could contribute to the strengthening of these approaches. We focused this review on the contributions of recent renowned mathematics historians that have had immersed in new findings related to the development of Algebra. In this paper, we present at least six considerations that can be problematized from the perspective of Mathematics Education, which generate new routes of investigation that could contribute significantly to a more robust and profound understanding of algebraic activity in general, and positively impact on the understanding of development of algebraic activity in mathematical education.